KEBIJAKAN PENGELOLAAN ANGGARAN PENDIDIKAN DI KABUPATEN LOMBOK TENGAH - Siti Sanisah (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2015)
The research aimedat exploring the education budget policies that carried out in the context of regional autonomy concerning to: formulation, content, implementation, evaluation and policy impact.The research was qualitative and using deep interviews,observations and focus group discussions.The source of information were the related staffs of Educational Board, Regional Development Planning Bureau, Local government and legislatives in Lombok Tengah which then run on purposive and snowball sampling technique. It was concluded that formulation stages applied three main approaches namely participatory, technocratic and political. The contents of the budget policymet the demands of budgeting regulation (20%), but still focus on infrastructure development and bureaucratic spending. The implementation process using a top down approach that automatically implementer predominantly from government agencies. The resultswere still below of the standards (criteria) that have been defined previously on planning stage. Finally, the impact provided less social benefit to the community. Keywords: policy of analysis and educational budgeting